2017
DOI: 10.5604/12321966.1235180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance of <i>Salmonella</i> in meat and meat products in Latvia

Abstract: Terentjeva M, Avsejenko J, Streikiša M, Utināne A, Kovaļenko K, Bērziņš A. Prevalence and antimicrobial resistance of Salmonella in meat and meat products in Latvia. Ann Agric Environ Med. 2017; 24(2): 317-321. AbstractIntroduction and objective. Salmonella is a foodborne pathogen which causes gastrointestinal illness in consumers, and exhibits resistance to antimicrobials of veterinary and clinical significance. The aim of this study is to detect the prevalence and antimicrobial resistance of Salmonella isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
4
11
2
4
Order By: Relevance
“…The non confirmation of positivity at the microbiological analysis in the environmental samples not in contact with meat, that were positives at real-time PCR, shows the effectiveness of good hygiene practices during pre and post operative cleaning phases. Overall, data on the prevalence of Salmonella spp concerning environments, products and Salmonella typing obtained in this work confirm the ones reported in literature (D’ostuni et al , 2016; Terentjeva et al , 2017). As demonstrated by several research, our study demonstrated that the most common Salmonella serovariant isolated from pig in the EU are Salmonella Typhimurium, Salmonella Derby and monophasic serovariant of Salmonella Typhimurium (Bonardi, 2017; Barilli et al , 2018; EFSA and ECDC, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The non confirmation of positivity at the microbiological analysis in the environmental samples not in contact with meat, that were positives at real-time PCR, shows the effectiveness of good hygiene practices during pre and post operative cleaning phases. Overall, data on the prevalence of Salmonella spp concerning environments, products and Salmonella typing obtained in this work confirm the ones reported in literature (D’ostuni et al , 2016; Terentjeva et al , 2017). As demonstrated by several research, our study demonstrated that the most common Salmonella serovariant isolated from pig in the EU are Salmonella Typhimurium, Salmonella Derby and monophasic serovariant of Salmonella Typhimurium (Bonardi, 2017; Barilli et al , 2018; EFSA and ECDC, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, increasing AMR trends were published for TET in China [87.5% (Ren et al , 2017 ); 75.3% (Zhang et al , 2018 )], Thailand [73.3% (Sinwat et al , 2015 )], North Vietnam [58.5% (Thai et al , 2012 )] and the Czech Republic [100% (Myšková and Karpišková, 2017 )]; for SMX in Thailand (Sinwat et al , 2015 ) and Latvia (Terentjeva et al , 2017 ); for CIP in Latvia [24.0% (Terentjeva et al , 2017 )]; and for NAL in North Vietnam [28.8% (Thai et al , 2012 )]. Even if the recorded resistance level to another seven antibiotics, including AMP (35.3%), CHL (33.3%), TGC (25.5%), CTX (13.7%), CST (13.7%), TMP (7.8%), and GEN (2%) were moderate or low, the obtained results underscored a wide and worrying resistance spectrum of the Salmonella strains.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to those reported in other countries in Asia (Hyun-Jung [18, 19]), with S. Infantis as the main serovar. Although, the main serovar in some European countries was S. Typhimurium (Terentjeva et al [20], [21], Wierup et al [22]). The different Salmonella serovars present in broilers may depend on the region or country due to variations in climate, geographical regions and chicken husbandry practices among countries.…”
Section: Discussionmentioning
confidence: 99%